Oikeudelliset todistelunrajoitteet rikosasiassa - Jämsä, Jurkka; Helsingin yliopisto. Oikeustieteellinen tiedekunta (Helsinki : Suomalainen Lakimiesyhdistys, 2020)
Abstract.
The topic of this research is legal norms restricting the admissibility of evidence in Finnish criminal procedure. Its primary method is doctrinal but, in addition, epistemological and comparative notions are employed to broaden the view of the subject. Traditionally, Finnish legal research has used Scandinavian and German law as the point of comparison. Here, an attempt is made to focus more on the British and American law of evidence. This does not mean, however, that Scandinavia or Germany should be overlooked. The normative structure of the Finnish law of evidence has, after all, been influenced mostly by these.
It has been said that evidence law is a matter of epistemology, the philosophy of knowledge. The role of evidence is to provide grounds for knowledge with legal implications. For that reason, the basic maxim of free proof is to allow as much information in a trial as possible. Indeed, any limitation on evidence means a limitation on knowledge, and may have direct effects on a trial’s outcome. Against this background, the admissibility of evidence should only be restricted if its admission would jeopardise an interest even greater in weight than a correct outcome. A brief analysis of such interests is essential for understanding rules of admissibility.
For at least two decades now, praxis of the European Court of Human Rights (ECtHR) on the right to a fair trial has had a great impact on the development and interpretation of Finnish evidence law. As a result of this, it is important to recognise and analyse exactly what requirements for the use of evidence can and should be derived from this praxis. This research suggests that the traditional German framework of admissibility rules – which distinguishes between forbidden subjects, means, and methods of gathering and introducing evidence – needs to be modified in order to understand the latest developments.
The framework suggested in this research is based upon three variable elements that are common for all rules restricting the use of evidence. The traditional division is incorporated into the framework as its first element, pointing out the object of the restriction, i.e. what sort of use of evidence is being restricted. Secondly, it is important to recognise and distinguish between rigid rules forbidding a particular use from those more flexible that set conditions for using evidence. Should the conditions be met, the evidence may be used. Lastly, not all restrictions apply similarly (or at all) in all three stages of the procedure: pre-trial investigation, trial, and deliberation.
After outlining a framework, it is put into use by analysing the target, flexibility, and phase(s) of application of all legal norms restricting the freedom of proof. The main focus is on the ECtHR praxis, which is growing in importance but not comprehensively analysed. Using the new and more nuanced framework, an attempt is made to explain in greater detail the differences between the more traditional rules of admissibility on the one hand and those derived from the ECtHR’s judgements on the other. It is especially within these judgements that a greater flexibility is found in comparison to the established rules of admissibility such as various professional privileges.
Perhaps the most difficult and challenging rules of evidence are those resulting from the breaches of either the privilege against self-incrimination or the right to cross-examine prosecution witnesses. There are landmark judgements within the jurisprudence of the ECtHR on both subjects; yet, it seems that the Strasbourg Court has been unsuccessful in creating an understandable and practical model for evaluating the effects of these breaches. Another important attempt of this research is to clarify and interpret the ECtHR’s judgements in order to understand how these evaluations should be made. This would hopefully benefit not only academia, but the legal practitioners as well.
”Oikeudelliset todistelunrajoitteet rikosasiassa” on oikeustieteellinen väitöstutkimus, jossa tarkennetaan todistusoikeuden käsitteistöä ja yleisiä oppeja jäsentämällä Euroopan ihmisoikeustuomioistuimen ratkaisukäytännössä kehittyneitä periaatteita todistelunrajoitteista ja todisteen hyödyntämiskielloista suhteessa uudistettuihin, kansallisiin todistelua rajoittaviin säännöksiin.
Todistelun vapautta rajoittavien oikeusnormien vaikutusta pyritään kuvaamaan aikaisempaa monipuolisemmin ja kehittämään käsitteellinen viitekehys, jolla voidaan kuvata kaikkia oikeudellisia todistelunrajoitteita sekä niiden toimintatapaa. Perustana on tällaisten normien kolmen keskeisen ominaisuuden eli kohteen, joustavuuden ja ulottuvuuden erottaminen. Tutkimus on hyödyksi paitsi todistusoikeuden tutkijoille myös käytännön juristeille, jotka yhä useammin joutuvat arvioimaan oikeudellisten todistelunrajoitteiden soveltuvuutta ja vaikutuksia.
Johdanto -- Todistelu osana rikosprosessia -- Oikeudellisten todistelunrajoitteiden järjestelmä -- Yksittäisiä todistelunrajoitteita -- Todistamiskiellot -- Myötävaikuttamattomuusperiaate -- Todistusmetodikiellot -- Todisteen lainvastainen hankkiminen -- Todistelun kontradiktorisuus ja välittömyys -- Lopuksi.
Väitöskirja
Sisältää bibliografisia viitteitä ja hakemiston.
Keywords: lainoppi; todistusoikeus; todistelu; rikosprosessi; rajoitukset; normit; todisteet; Suomi; väitöskirjat